HUBUNGAN BULLYING DENGAN KESEHATAN MENTAL PADA REMAJA DI MTsS MIFTAHUN NAJAH KABUPATEN TANGERANG 2025 - sri Rahmawati sri (Jurnal Riset Media Keperawatan, 2026)
Background: Bullying has become a serious social issue in various circles, especially in the school environment. Bullying or bullying is an aggressive act that is repeatedly carried out by individuals or groups against others who are considered weaker than them. Research Objective: To find out the relationship between bullying and mental health in adolescents. Research Method: This study is a quantitative study using a descriptive correlation design with a cross sectional approach. From the total population of 135 students, a sample of 101 respondents was obtained using random sampling techniques. The statistical test uses a chi square. Results: The study obtained a P-value of 0.002<0.05 which means that there is a relationship between bullying and mental health in adolescents. Conclusion: There is a link between bullying and mental health in adolescents. Keywords: Bullying, Mental health